A Monte Carlo simulation for the estimation of patient dose in rest and stress cardiac computed tomography with a 320-detector row CT scanner. Issue 8 (December 2015) - Geleijns, Jacob; Joemai, Raoul M.S.; Cros, Maria; Hernandez-Giron, Irene; Calzado, Alfonso; Dewey, Marc; Salvado, Marçal
Highlights: Effective dose is 10–20 mSv for coronary CTA and myocardial rest- and stress imaging. Modifying the phantoms in accordance with clinical practice had a noticeable effect. k-factors may lead to underestimations of effective dose by a factor of 2–3. Effective dose in cardiac CT is relatively high for females. Abstract: Purpose: To estimate organ dose and effective dose for patients for cardiac CT as applied in an international multicenter study (CORE320) with a 320-Detector row CT scanner using Monte Carlo (MC) simulations and voxelized phantoms. The effect of positioning of the arms, off-centering the patient and heart rate on patient dose was analyzed. Methods: A MC code was tailored to simulate the geometry and characteristics of the CT scanner. The phantoms representing the adult reference male and female were implemented according to ICRP 110. Effective dose and organ doses were obtained for CT acquisition protocols for calcium scoring, coronary angiography and myocardial perfusion. Results: For low heart rate, the normalized effective dose (E) for cardiac CT was higher for female (5.6 mSv/100 mAs) compared to male (2.2 mSv/100 mAs) due to the contribution of female breast tissue. Averaged E for female and male was 11.3 mSv for the comprehensive cardiac protocol consisting of calcium scoring (1.9 mSv); coronary angiography including rest cardiac perfusion (5.1 mSv) and stress cardiac perfusion (4.3 mSv). These values almost doubled at higher heart rates (20.1 mSv). Excluding the arms increased effective dose by 6–8%, centering the patient showed no significant effect. The k-factor (0.028 mSv/mGy.cm) derived from this study leads to effective doses up to 2–3 times higher than the values obtained using now outdated methodologies. Conclusion: MC modeling of cardiac CT examinations on realistic voxelized phantoms allowed us to assess patient doses accurately and we derived k-factors that are well above those published previously.